2009
DOI: 10.3748/wjg.15.3376
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to differentiate gastric GISTs from gastric leiomyomas by EUS?

Abstract: EUS may help to differentiate gastric GISTs from gastric leiomyomas. Once GISTs are suspected, surgery should be considered if the size is greater than 3.5 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 17 publications
8
85
1
5
Order By: Relevance
“…Echogenicity is usually associated with a histology of cellularity and homogeneity of the lesion in other solid organs [21][22][23]. Although correlation studies of US and histopathology in thyroid nodules are rare, it was thought that hypoechogenicity was due to compaction, fibrosis, and high cellularity [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Echogenicity is usually associated with a histology of cellularity and homogeneity of the lesion in other solid organs [21][22][23]. Although correlation studies of US and histopathology in thyroid nodules are rare, it was thought that hypoechogenicity was due to compaction, fibrosis, and high cellularity [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…On EUS ( Figure 1C, D), a GIST is typically a well-circumscribed, hypoechoic, relatively homogeneous mass that can arise from either the second hypoechoic layer (muscularis mucosa) or more frequently the fourth hypoechoic layer (muscularis propria). In addition to size and mucosal ulcer, other EUS characteristics have been considered as possible predictive factors, but size is the only consistently definitive predictive factor [45][46][47][48]. One study suggested that GISTs have a marginal hypoechoic halo and relatively higher echogenicity compared with the adjacent muscular layer [49].…”
Section: Gastrointestinal Stromal Tumors (Gist)mentioning
confidence: 99%
“…Leiomyomas appear endosonographically as small (< 5 cm) homogenous, hypoechoic SMTs, with smooth/distinct borders, originating from the forth or second wall layer [8] . Signs like inhomogenicity, hyperechogenic spots, a marginal halo and higher echogenicity compared to the surrounding muscle layer might appear more frequently in GISTs than in leiomyomas [35] , but differentiation based merely on imaging is risky and therefore should be done only in specific conditions and with the informed of the patient. For larger lesions, surgical resection seems to be the best alternative; (2) Extrinsic compressions: Compressions on the gastric wall from organs neighboring the stomach may occasionally present as SMLs and sometimes can cause diagnostic problems.…”
Section: Miscellaneous Smls In Eusmentioning
confidence: 99%